Factors that influence value creation and value capture in companies: Evidence in an emerging market - Jhony Ostos; Manuel-Fernando Montoya-Ramírez (Journal of Economics, Finance and Administrative Science, 2025)
Purpose - The objective of this study is to analyze the influence of the following variables - technological innovation, creativity and innovation management and business model innovation - on two variables: value creation in companies and value capture in companies. Design/methodology/approach - The sample consisted of 222 informants employed by companieslisted in the Top 1,000 in the city of Lima. A questionnaire was designed to examine the five variables under study (three independent variables and two dependent variables). Confirmatory and structural factor analyses were performed using structural equations with the SPSS AMOS software. Findings - The study shows that value capture is influenced by technological innovation, creativity and innovation management, as well as business model innovation, while value creation is influenced only by technological innovation and business model innovation. Research limitations/implications - One limitation of this study is that its results are generalized for companies from different business sectors, so its conclusions cannot be associated with specific business sectors. Another limitation of the study isthat the data from thisresearch are cross-sectional,so the relationships found between the study variables are not sufficient to establish a definitive causal relationship. Practical implications - For executives, this study offers valuable insights into the significance of their management roles in driving innovation, particularly concerning the dual objectives of value creation and capture within their organizations. Originality/value - A research model is proposed to identify the factorsthat influence value creation and value capture in companies in a developing country, where consumers have different purchasing power and purchasing preferences compared to consumers in developed countries. Executives focus their efforts on creating and implementing innovative ideas only if they perceive that doing so will achieve monetary results, and it is necessary to emphasize the innovation of internal processes to create value in a way customers will perceive.
Keywords: M1; O32; 330; Technological innovation; Innovation; Creativity; Business models; Value creation in companies; Value capture in companies